Residential demand estimation for bundled fixed-line and wireless mobile broadband services - Madden, Gary; Suphachalasai, S.; Makjamroon, T. (Routledge, 2015)
This article is the first investigation of residential Internet markets in Thailand, in particular Bangkok. Bangkok is an interesting market to study as it is Thailand’s most populous province, and supports an advanced economy. The study offers a comprehensive discussion of the process to obtain cross-price elasticity estimates when Internet services are bundled. Interestingly, the empirical results reveal positive cross-price effects, i.e. Internet alternatives are viewed as substitutes by respondents in this market. This finding is plausible as the services differ essentially in their model of delivery.